Deregulation of cell growth and apoptosis in UV-induced melanomagenesis - Allal Ouhtit; Ishita Gupta; Rajiv L. Gaur; Augusta Fernando; Amira O. Abd El-Azim; Ali Eid; Therese M Becker (Frontiers in Bioscience-Elite, 2020)
We have previously characterized the role of p16/Rb in coordinating the early events in UVB-irradiated skin. As an extension to this work, normal melanocytes and mutant p16-inducible melanoma cell models were employed to elucidate further the coordinated molecular mechanisms occurring during early UVB exposure. Our results showed that melanocytes expressed p16 only at a high UVB dose, with undetectable p53. The Bax/Bcl2 ratio increased at higher dose, indicating that the cells had selected apoptosis program. In the wt-p16 melanoma cells, while low UVB dose upregulated p16, the high dose suppressed it, and further abrogated Cdk6 but not Cdk4. Interestingly, while induction of mutant-p16 increased Cdk4, cdk6 and pRb proteins, UVB exposure did not affect this increase. More interestingly, p16 mutant cells increased their resistance to apoptosis at high UVB-dose, associated with decreased Bax and increased Bcl2 expression. Thus, mutant-p16 appears to dictate a deregulation of cell cycle and increased resistance to apoptosis in melanoma cells. Together, the data indicate a deregulation of p16INK4/Rb pathway as an early event in UVB-induced melanomagenesis.